Effect of acupuncture for non-motor symptoms in patients with Parkinson’s disease: A systematic review and meta-analysis - Li, Qinglian; Wu, Chunxiao; Wang, Xiaoling; Li, Zhen; Hao, Xiaoqian; Zhao, Lijun; Li, Mengzhu; Zhu, Meiling (Frontiers in Aging Neuroscience, 2022)
Background: Although nonmotor symptoms of Parkinson’s disease (PD) are serious, effective treatments are still lacking. Acupuncture may have clinical benefits for nonmotor symptoms of PD patients, but high-quality evidence supporting this possibility is still limited. Hence, we conducted this meta-analysis to evaluate the effect of acupuncture treatment on nonmotor symptoms in patients with PD. Methods: Randomized controlled trials (RCTs) of acupuncture treatment for PD were retrieved from the following electronic databases: Medline (OVID), Embase (OVID), Cochrane Library, Web of Science, China National Knowledge Infrastructure, Chinese BioMedical Literature Database, Chonqing VIP (CQVIP), and Wangfang Database. Studies evaluating nonmotor symptoms of PD were retrieved. Methodological quality was assessed using the Cochrane Handbook for Systematic Reviews of Interventions. Results: A total of 27 RCTs were included, among which 8 outcomes related to nonmotor symptoms were evaluated. The results showed that acupuncture combined with medication had benefits for PD-related insomnia relative to control (standardized mean difference [SMD] =0.517; 95% confidence interval [CI] = 0.242–0.793; p = 0.000), and acupuncture treatment had benefits at 8 weeks (SMD = 0.519; 95% CI = 0.181–0.857; p = 0.003). Regarding depression, acupuncture treatment was more effective (SMD = -0.353; 95% CI = -0.669– -0.037; p = 0.029) within 2 months (SMD = -0.671; 95% CI = -1.332– -0.011; p = 0.046). Regarding cognition, quality of life, and Unified Parkinson's Disease Rating Scale (UPDRS) Ⅰ and II scores, acupuncture treatment was effective (SMD = 0.878, 95% CI = 0.046–1.711, p = 0.039; SMD = -0.690, 95% CI = -1.226– -0.155, p = 0.011; weighted mean difference (WMD) = -1.536, 95% CI = -2.201– -0.871, p = 0.000; WMD = -2.071, 95% CI =-3.792– -0.351, p = 0.018; respectively). A significant difference was not found in terms of PD-related constipation. Only one study evaluated PD-related fatigue. Conclusion: The results of the analysis suggested that acupuncture treatment could ameliorate the symptoms of depression, quality of life, cognition, total mentation, behaviour and mood, and activities of daily living in PD patients. Nevertheless, more prospective, well-designed RCTs with larger sample sizes are required to confirm our findings.